Integration of KH Imam Zarkasyi's Independence Values in Differentiated Learning of the Independent Curriculum - Habib, Mursyid; Salsabila, Puja; Miftahuddin, Miftahuddin (UIR Press, 2026)
This study explores the systematic integration of KH Imam Zarkasyi's philosophical Independence Values (Gontor Modern Islamic Boarding School) with the Differentiated Learning framework in the implementation of the Independent Curriculum in Indonesia. The Independent Curriculum prioritizes Differentiated Learning as a student centered pedagogical approach, which automatically demands a high level of self regulation from students. Although the independence values of Islamic boarding schools have proven successful in building students' self regulating character, there is a significant gap in the literature regarding the integration of this traditional educational philosophy with modern approaches such as differentiation. Through a qualitative descriptive approach with a literature review, this article aims to formulate a strategic integration model. The results show that integration is achieved by strengthening three elements of differentiation using Gontor values, Process Differentiation strengthened by the concepts of Self Reliance and Discipline that shape responsible freedom, Product Differentiation strengthened by the principles of Initiative, Independence, and Adab to ensure the originality and usefulness of the work, and Content Differentiation strengthened by the principle of Itqan (complete mastery) to ensure all students achieve a fundamental understanding before undertaking further exploration. This integration results in a holistic learning ecosystem, where student freedom is framed by strong moral and academic standards, strengthening the identity and relevance of national education.